(untitled) (Research, Society and Development, 2023)
Objective: To identify the prevalence and mortality of hospitalizations for musculoskeletal injuries due to traffic accidents in Brazil. Methods: This is a retrospective clinical investigation, through a quantitative epidemiological study, whose data were obtained by consulting the databases Departamento de Informática do Sistema Único de Saúde (DATASUS). The study sample were patients hospitalized victims of traffic accidents involving musculoskeletal injuries in Brazil during the years 2018 to 2022. Results: 1,118,984 cases of musculoskeletal injuries due to traffic accidents were recorded during the period 2018-2022 in Brazil. The most involved age group was 20 - 40 years (48.7%), children and adolescents comprised a large part of this population (14.8%). 142,130 deaths were recorded. Conclusion: Musculoskeletal injuries due to traffic accidents result in significant socioeconomic impacts, and the insertion of social policies aimed at monitoring and risk reduction is essential.